Reconstruction of the Correctional System within the Framework of Criminal Justice - Taufik Tri Prabowo; Abudllah Sulaiman (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
This study aims to analyze the reconstruction of the correctional system within Indonesia’s criminal justice framework following the enactment of Law Number 22 of 2022 on Corrections. The shift from Law Number 12 of 1995 to the new regulation marks a significant paradigm change in penal policy-from a narrow interpretation focused on imprisonment to a broader correctional approach that is more corrective, rehabilitative, and restorative. Employing a normative legal research method with conceptual and statutory approaches, this study explores the evolving roles, responsibilities, and positioning of corrections within the entire criminal justice process, from pre-adjudication to post-adjudication stages. The findings indicate that the previous construction of corrections as merely executing custodial sentences is outdated and no longer compatible with legal developments, social dynamics, or contemporary demands for human rights protection. Law No. 22 of 2022 expands the mandate of corrections as a penitentiary system integrated with other key regulations such as the Penal Code (KUHP), Criminal Procedure Code (KUHAP), and Juvenile Justice Law (UU SPPA). Consequently, a redefinition of the concept, structure, and function of corrections is required to ensure adaptability, institutional effectiveness, and alignment with modern penal paradigms. This study concludes that the reconstruction of Indonesia’s correctional system must be understood as a systemic transformation, not merely an administrative revision, to support a more humane, transformative, and nationally contextualized criminal justice system.